Two new fish species of the genus Toxabramis Gunther, 1873 (Cyprinidae, Cypriniformes) from Vietnam - Ngoc, Duong Quang; Duc, Nguyen Huu; Hau, Tran Duc; Thuy, Ta Thi (Academia Journal of Biology, 2014)
Six species of the genus Toxabramis Gunther, 1873 (Cyprinidae, Cypriniformes) were found; among them two species were new for science. In the paper, the description of these new species is presented and a key to identify the known species of these genus is established. 1. Toxabramis maensis H. D. Nguyen & Q. N. Duong sp.nov. is found in the Ma river (Quanhoa and Thieuhoa districts, Thanhhoa province, Vietnam) Body elongate, strongly compressed. Head comparatively small. Mouth small. Oblique. Uper jaw prominent. Dorsal fin short, its origin behind that of ventral fin and near origin of caudal fin than top of rostral. Unbranched dorsal fin rays well ossified, denticulated behind. Anus immediatly in front of origin of anal fin. Lateral line complete. Coloration: body silvery; back dark. A dark axial lateral stripe running from the gill opening to the base of the caudal fin. Remarks: This species is near with Toxabramis hotayensis Hao, 2001, T. houdmeri Pellegrin, 1932 and T. nhatleensis sp.nov. but there are some different characteristics: the number of gill rakers on the first branchial arc of this species are more in comparison with other species of the genus; its number of lateral line scales are more in comparison with two species T. hotayensis and T. nhatleensis; its number of denticulate ossified unbranched dorsal fin rays are more in comparison with T. nhatleensis (table 1). 2. Toxabramis nhatleensis H. D. Nguyen, D. H. Tran & T. T. Ta sp.nov. is found in the Nhatle river (Lethuy district, Quangbinh province, Vietnam). Body elongate; Mouth small, comparatively oblique. Dorsal fin short, it’s origin behind that of ventral fin and its origin near of origin of caudal fin than top of the rostril. Unbranched dorsal fin rays well ossified, denticulated behind. Anus immediatly in front of origin of anal fin. Lateral line comlete. Coloration: body silvery; back dark. A dark axial lateral stripe running from the gill opening to the tip of the middle caudal fin rays. Remarks: this species is near with T. maensis H. D. Nguyen & Q. N. Duong sp.nov., T. houdmeri Pellegrin, 1932 and T. hotayensis Hao, but there are some different characteristics: the number of gill rakers of this species are more in comparison with T. hotayensis and its number of denticulate ossified unbranched dorsal fin rays are less than in T. hotayensis; its number of scales, gill rakers and denticulate ossified unbranched dorsal fin rays are less than in T. maensis (table 1).